Dimethyl fumarate modulates the Treg–Th17 cell axis in patients with psoriasis*. (1st March 2021) - Sulaimani, J.; Cluxton, D.; Clowry, J.; Petrasca, A.; Molloy, O.E.; Moran, B.; Sweeney, C.M.; Malara, A.; McNicholas, N.; McGuigan, C.; Kirby, B.; Fletcher, J.M.
Summary: Background: Dimethyl fumarate (DMF) is the active ingredient of Skilarence™ and Tecfidera™, which are used for the treatment of psoriasis and multiple sclerosis, respectively. Various immunomodulatory mechanisms of action have been identified for DMF; however, it is still unclear what effects DMF exerts in vivo in patients with psoriasis. Objectives: In this study we examined the effects of DMF, both in vivo and in vitro, on T cells, which play a key role in the pathogenesis of psoriasis. Methods: The frequency of T‐cell subsets was examined by flow cytometry in untreated patients with psoriasis or those treated with DMF. The effects of DMF in vitro on T‐cell survival, activation and proliferation, and cell‐surface thiols were assessed by flow cytometry. Results: In patients with psoriasis treated with DMF we observed an increase in the frequency of T regulatory (Treg) cells and a decrease in T helper (Th)17 lineage cells and the associated cytokines interleukin‐17, interleukin‐22 and granulocyte–macrophage colony‐stimulating factor. T cells cultured in vitro with DMF exhibited reduced viability, and inhibition of activation and proliferation in response to stimulation due to the oxidative effects of DMF. However, the frequency of Treg cells increased in the presence of DMF due to their heightened ability to resist DMF‐induced oxidative stress. Conclusions: DMF enhanced the ratio of Treg cells to Th17 cells in patients with psoriasis, in patients with multiple sclerosis and in vitro . Furthermore, our data suggest that this is at least in part as a result of the differential effects of DMF on Treg cells compared with conventional T cells.